Pengaruh Lama Penyimpanan terhadap Kualitas Sambal Nanas (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2025)
Pineapple sambal, a traditional dish from Jambi, is known for its spicy and tangy flavors but has a short shelf life due to its high water and acid content. This study analyzes the effect of shelf life on the quality of pineapple sambal (color, aroma, taste, and texture) using a pure experimental method and ANOVA analysis at room temperature (25–30°C) over a period of 1–7 days. The results indicate significant differences in all sensory parameters (p < 0.05). The best quality was observed from the first to the third day, with a significant decline starting on the fourth day. By the fifth day, the fresh aroma shifted to an undesirable sour smell, the texture became mushy, and the color faded due to microbial activity and oxidation. These findings are relevant to the food industry for developing airtight packaging or cold storage solutions. The study concludes that the optimal shelf life of pineapple sambal at room temperature is three days, supporting the preservation of Jambi's culinary heritage and its development into a competitive commercial product.